Estimation of Sustained Groundwater Resource Potential by Analyzing Aquifer Depth Lithology in Selebar Subdistrict, Bengkulu - Fadilah Fadilah; Marulak Simarmata; Muchammad Farid; Sukisno Sukisno (Postgraduate, University of Mataram, 2025)
Rapid urban development frequently overlooks groundwater availability, potentially causing environmental degradation and unsustainable resource management. This study aims to determine groundwater potential through geoelectric resistivity analysis in Selebar Subdistrict, Bengkulu, specifically at Fatmawati Sukarno State Islamic University campus area. The Schlumberger configuration method was employed across four measurement tracks, with electrode spacing systematically varied to detect subsurface resistivity variations at depths up to 300 meters. Data were processed using Progress Version 3.0 software, applying both direct and indirect interpretation methods through inversion techniques. Laboratory analysis of water samples assessed physical and chemical parameters including pH, turbidity, Total Dissolved Solids (TDS), color, odor, and temperature against Minister of Health Regulation No. 32/2017 standards. Results identified two distinct aquifer systems: an unconfined aquifer at 9.94-25.53 meters depth with 15.59 meters thickness, and a confined aquifer exceeding 161.43 meters depth. Resistivity values ranged from 0.93 to 6.74 ohm-m, indicating water-bearing clayey sandstone formations. Water quality analysis demonstrated that samples from three locations met drinking water standards, while the Student Center location exhibited elevated pH (8.64), rendering it unsuitable for direct consumption but acceptable for non-potable applications